Methylation patterns in serum DNA for early identification of disseminated breast cancer - Widschwendter, Martin; Evans, Iona; Jones, Allison; Ghazali, Shohreh; Reisel, Daniel; Ryan, Andy; Gentry-Maharaj, Aleksandra; Zikan, Michal; Cibula, David; Eichner, Johannes; Alunni-Fabbroni, Marianna; Koch, Julian; et al. (Genome medicine, 2017)
BACKGROUND: Monitoring treatment and early detection of fatal breast cancer (BC) remains a major unmet need. Aberrant circulating DNA methylation (DNAme) patterns are likely to provide a highly specific cancer signal. We hypothesized that cell-free DNAme markers could indicate disseminated breast cancer, even in the presence of substantial quantities of background DNA. METHODS: We used reduced representation bisulfite sequencing (RRBS) of 31 tissues and established serum assays based on ultra-high coverage bisulfite sequencing in two independent prospective serum sets (n = 110). The clinical use of one specific region, EFC#93, was validated in 419 patients (in both pre- and post-adjuvant chemotherapy samples) from SUCCESS (Simultaneous Study of Gemcitabine-Docetaxel Combination adjuvant treatment, as well as Extended Bisphosphonate and Surveillance-Trial) and 925 women (pre-diagnosis) from the UKCTOCS (UK Collaborative Trial of Ovarian Cancer Screening) population cohort, with overall survival and occurrence of incident breast cancer (which will or will not lead to death), respectively, as primary endpoints. RESULTS: A total of 18 BC specific DNAme patterns were discovered in tissue, of which the top six were further tested in serum. The best candidate, EFC#93, was validated for clinical use. EFC#93 was an independent poor prognostic marker in pre-chemotherapy samples (hazard ratio [HR] for death = 7.689) and superior to circulating tumor cells (CTCs) (HR for death = 5.681). More than 70% of patients with both CTCs and EFC#93 serum DNAme positivity in their pre-chemotherapy samples relapsed within five years. EFC#93-positive disseminated disease in post-chemotherapy samples seems to respond to anti-hormonal treatment. The presence of EFC#93 serum DNAme identified 42.9% and 25% of women who were diagnosed with a fatal BC within 3-6 and 6-12 months of sample donation, respectively, with a specificity of 88%. The sensitivity with respect to detecting fatal BC was ~ 4-fold higher compared to non-fatal BC. CONCLUSIONS: Detection of EFC#93 serum DNAme patterns offers a new tool for early diagnosis and management of disseminated breast cancers. Clinical trials are required to assess whether EFC#93-positive women in the absence of radiological detectable breast cancers will benefit from anti-hormonal treatment before the breast lesions become clinically apparent.
Keywords: DNA Methylation; metylace DNA; Neoplastic Cells, Circulating; Adult; Aged; dospělí; nádorové cirkulující buňky; nádory prsu; senioři; lidé středního věku; lidé; ženské pohlaví; Breast Neoplasms; Humans; volné cirkulující nukleové kyseliny; Cell-Free Nucleic Acids; Female; Biomarkers, Tumor; nádorové biomarkery; Middle Aged